Importance of the work on preservation, restoration and propagation of architectural monuments in Khorezm region in the development of spirituality - Rajabova Zuxra Sa’dullaevna; D.B. Bobojonova. (Proceedings of The ICECRS, 2019)
In it article, the author states research on tourist potential to the Republic of Uzbekistan. About opportunity having success, and a task in the future for today’s day. Soberly and with a new view states change, reforms in it to branch. And also the author offers in rows the offer and the instruction.